DEVELOPMENT OF TECHNOLOGY FOR THE EXTRACTION OF LEAD AND ZINC OXIDES FROM DUST AND SLAGS DURING THE UTILIZATION OF LEAD PLANT WASTE - K. Zhantassov; Z. Bagova; G. Turebekova; B. Sapargaliyeva; G. Pusurmanova (Academic Scientific Journal of Chemistry, 2021)
The object of the study is lead-containing slag dumps from a lead plant. The slags of the lead plant contain a large number of toxic compounds: lead, zinc, osmium, cadmium, which are dangerous sources of environmental pollution. Due to the open storage of slags, it was found that the maximum permissible concentrations of lead were exceeded. Utilization of lead production slags allows to obtain non-ferrous metals and to reduce the technogenic load on the environment as a result of processing of slags. At the same time, slags are valuable raw materials containing compounds of non-ferrous and rare-earth metals. The article proposes methods for the extraction of lead and zinc from slag waste and selects the optimal method for the selective extraction of zinc and lead oxides from dust and slags of lead production. The proposed technology of continuous carbon-free selective extraction of zinc and lead from the dust of electric steelmaking production allows the use of lead production slag, which is fed into a rotating drum furnace in two oppositely directed streams. During the movement of lead slag in the furnace drum and the burning of the torch, lead and zinc are more completely extracted from the dust-like material, where the transporting object is compressed air, and the purified flue gas after the gas is further purified by means of a smoke pump is released into the atmosphere. When using the proposed selective method for extracting non-ferrous metals, the ecological state of the environment will be improved, and it will also reduce the negative impact on human health due to the disposal of toxic slags from lead production